Correction of insulin resistance in patients with chronic obstructive pulmonary disease under the influence of recovery treatment - O.I. Lemko; N.V. Vantiukh; D.V. Reshetar; S.V. Lukashchuk (Medičnì Perspektivi)
According to modern concepts chronic obstructive pulmonary disease (COPD) is accompanied by persistent respiratory symptoms, as well as extrapulmonary systemic manifestations. Insulin resistance and metabolic syndrome belong to the leading causes of comorbidity formation. The aim is to study the possibilities of insulin resistance correction in COPD patients, taking into account the previous COVID-19, under the influence of complex non-pharmacological treatment based on haloaerosoltherapy in connection with the applied treatment complex. Clinical and functional examinations and carbohydrate metabolism investigations were carried out in 115 patients with COPD (GOLD II-III) beyond the acute period before and after the course of recovery treatment. Among them 60 patients were convalescents after COVID-19. The average age of patients was 60,3±1,71 years and duration of COPD – 14,2±0,89 years. A control group 12 practically healthy persons were also examined. The presence of insulin resistance was diagnosed by evaluation of the glucose, insulin, HOMA-IR index and C-peptide levels. Treatment was carried out according to three treatment complexes. The main component of the treatment was the use of haloaerosoltherapy and its combination with singlet oxygen therapy or drinking and inhalation of mineral water. The duration of the course of treatment was 20-21 days. Before treatment the presence of insulin resistance was confirmed in both groups of patients with COPD (without COVID-19 and convalescents after COVID-19). Blood glucose levels were significantly higher in the latter group. After the course of recovery treatment a decrease in insulin resistance was noted, especially in patients who received complex treatment, although complete normalization of the studied indices was not achieved. Thus, insulin resistance is a characteristic, pathogenetically determined metabolic manifestation in COPD, which requires constant monitoring and development of long-term programs of complex clinical management of this contingent of patients, especially beyond the exacerbation period. The use of haloaerosoltherapy, which has a sanative and anti-inflammatory effect and promotes clinical stabilization of COPD, is accompanied by a decrease in the manifestations of insulin resistance. Expressiveness of these changes depend on the applied treatment complex. The most pronounced decrease in insulin resistance in COPD patients was noted in a complex treatment based on haloaerosoltherapy with additional drinking and inhalation use of low-mineralized hydrocarbonate siliceous mineral water.